Sex-Based Medicine Meets Psoriatic Arthritis: Lessons Learned and to Learn - Bragazzi, Nicola Luigi; Bridgewood, Charlie; Watad, Abdulla; Damiani, Giovanni; McGonagle, Dennis (Frontiers in Immunology, 2022)
Sex and gender are concepts that are often misunderstood and misused, being utilized in a biased, preconceived, interchangeable way. However, sex is a biological variable linked to genetic (the chromosomal complement) and post-genetic, endocrinological (the hormonal complement), and phenotypic/anatomic (reproductive organs) components, whereas gender refers to one's personal self-identification/self-declaration as profoundly influenced by an array of societal, cultural, political, psychological, and biographic/personal experiences. Both sex and gender variables and their subtle, complex, and non-linear interactions can dramatically influence health-related outcomes. The present review overviews the current knowledge of sex-specific differences related to psoriatic arthritis, a chronic, inflammatory condition associated with cutaneous psoriasis and can be conceived as a wide clinical phenotype. Sex and gender-specific differences have implications for clinical research and practice. However, they are overlooked in several biomedical disciplines, including the rheumatological arena. Contrasting findings have been reported for psoriatic arthritis in terms of epidemiology (incidence, prevalence, lifetime risk, survival and mortality), clinical, radiological and laboratory features, and response to treatment. This may reflect subtle, complex, nonlinear interactions between the biological make-up of the individual (genetic and post-genetic complements), hormonal components, environmental exposures, and psychological variables. On the other hand, this reflects also the heterogeneity and paucity of data concerning sex-specific differences, which would be of crucial importance in achieving the ambitious goals of personalized/individualized medicine. Collaborative networking, international registries, standardized meta-data and Big Data could help disentangle and elucidate the precise mechanisms underlying sex-specific differences in psoriatic arthritis and advance a customized treatment and management, identifying specific endotypes/sub-phenotypes.